PENERAPAN TEORI BELAJAR SIBERNETIK DALAM PROSES PEMBELAJARAN PAI PADA MASA PANDEMI COVID 19 DI SMP NEGERI 54 PALEMBANG - Nur Azizah; Nyayu Khodijah; Aida Imtihana; Nurlaila Nurlaila (Jurnal PAI Raden Fatah, 2022)
Outbreak cases of pandemic covid 19 when it makes the student to shift the activities of learning to teach for a while time diverted home respectively. To prevent the spread of covid 19 inenvironmental education, then held learning distance away in the network (Online). The low ability of student in Islamic Religios Education Subjects and the lack of student and teacher interaction during the Covid 19 pandemic can slow down the formation of values ​​in teaching and learning. The objectives of this research are 1). To find out the application of cybernetics learning theory in the learning process of Islamic Religious Education during the Covid 19 pandemic at SMP Negeri 54 Palembang. 2). To find out the obstacles to the application of cybernetics learning theory in the learning process of Islamic Religious Education during the Covid 19 pandemic at SMP Negeri 54 Palembang. This type of qualitative research with a descriptive approach. Data collection techniques were carried out by observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusions. The results showed: (1) The application of cybernetics learning theory in the teaching and learning process is to determine instructional objectives, determine the subject matter, study the information systems contained in the material, and determine the learning approach that is in accordance with the information system, arrange the material in an order according to the system. information, presenting material, and guiding students to learn in a pattern that is in accordance with the sequence of lessons. (2) Constraints in the application of cybernetics learning theory during the Covid 19 pandemic, namely the ineffectiveness of internet network access, quotas, difficulty understanding the subject matter, inadequate technology, and Lack of teacher's ability to operate digital technology.